2013
DOI: 10.1002/ejic.201201077
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Perspectives on Redox “Non‐Innocent” Oxazolidine N‐Oxide Iron Nitroxide Complexes

Abstract: One‐electron redox processes in ligands that exhibit non‐innocent behaviour invariably leads to the generation of radical species, which, when coupled with redox‐active metal centres, can lead to strong magnetic exchange, ambiguous electronic structures and even spin crossover (SCO). We have chosen two iron complexes [FeII(L·)2](BF4)2 (1) and [FeIII(L–)2](BPh4) (2) [with L· = 4‐dimethyl‐2,2‐di(2‐pyridyl)oxazolidine N‐oxide] as the basis for an extensive theoretical study to determine the influence and interpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 69 publications
4
20
1
Order By: Relevance
“…The magnetic exchange interaction between O 2 C À and the Cr III ion is computed to be antiferromagnetic in nature (À1176.3 cm À1 ) and this suggests a triplet ground state for this species. [12] For this species a strong p-type interaction between the Cr(d xz ) and the oxygen p* orbital, and a relatively weak interaction between the Cr(d xy ) and oxygen p* orbital are estimated. These interactions are essentially a result of the nonlinear Cr III -O-O bond angle, and the non-orthogonality and strong mixing lead to a relatively strong antiferromagnetic interaction.…”
Section: Fementioning
confidence: 99%
“…The magnetic exchange interaction between O 2 C À and the Cr III ion is computed to be antiferromagnetic in nature (À1176.3 cm À1 ) and this suggests a triplet ground state for this species. [12] For this species a strong p-type interaction between the Cr(d xz ) and the oxygen p* orbital, and a relatively weak interaction between the Cr(d xy ) and oxygen p* orbital are estimated. These interactions are essentially a result of the nonlinear Cr III -O-O bond angle, and the non-orthogonality and strong mixing lead to a relatively strong antiferromagnetic interaction.…”
Section: Fementioning
confidence: 99%
“…It is known that the DFT methods might misestimate the covalent character of metal-ligand bonds [81][82][83]. Although this is more frequently the case of transition metal coordination compounds, we decided to calculate the Dg tensors with a vast array of functionals (UBP86, UPBE, UOLYP, UB3LYP, UPBE0).…”
Section: G Tensormentioning
confidence: 99%
“…[22] A second study by the latter authors added to these three systems CASPT2 results for the [Fe II (N H S 4 )L] series, [23] which indicated that OLYP performed better than PBE0 (25 % HF exchange), B3LYP, and B3LYP*, although all four DFT methods give identical trends (vide infra). Ghosh and coworker also favour OLYP, albeit they tested it on somewhat different systems including Fe III porphyrins, [24,25] as do Tewary et al [26] for the interesting case of computing magnetic exchange interactions and their possible effects on SCO, which involves "non-innocent" oxazolidine N-oxide iron nitroxide complexes.…”
Section: Introductionmentioning
confidence: 99%